2016
DOI: 10.1093/jac/dkw419
|View full text |Cite
|
Sign up to set email alerts
|

Community carriage of ESBL-producingEscherichia coliis associated with strains of low pathogenicity: a Swedish nationwide study

Abstract: E. coli host factors previously associated with higher pathogenicity were all more common in BSIs compared with carriers. This indicates that the risk of invasive infection with EPE may be relatively modest in many community carriers and that EPE carriage of high-risk strains should be the focus of attention for prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
60
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 34 publications
19
60
2
Order By: Relevance
“…In this study, the combined detection frequency of CPE/K and ESCE/K in stool from adult females was significantly higher compared with adult males. This contrasts to community carriage in Western Europe where no difference between genders was observed (Ny et al, 2017;Valenza et al, 2014;Wielders et al, 2017).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In this study, the combined detection frequency of CPE/K and ESCE/K in stool from adult females was significantly higher compared with adult males. This contrasts to community carriage in Western Europe where no difference between genders was observed (Ny et al, 2017;Valenza et al, 2014;Wielders et al, 2017).…”
Section: Discussioncontrasting
confidence: 77%
“…In this study, the combined detection frequency of CPE/K and ESCE/K in stool from adult females was significantly higher compared with adult males. This contrasts to community carriage in Western Europe where no difference between genders was observed (Ny et al, ; Valenza et al, ; Wielders et al, ). Furthermore, ESBL colonization in male neonatal children was more common compared with female neonatal children in an Israeli hospital (Leikin‐Zach et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…In the current study, the E. coli isolates carried bla CTX-M-55 and bla CTX-M-27 in addition to the bla CTX-M-1 (Table 1). Among humans in Sweden, the genes bla CTX-M-15 , bla CTX-M-14 , bla CTX-M-27 and bla CTX-M-1 are the most frequently detected, but the bla CTX-M-55 is rare [15]. Furthermore, the bla CTX-M-55 has been identified from wild-birds and pigs in Sweden, confirming that it occurs in Sweden and within different settings [10,23,24].…”
Section: Resultsmentioning
confidence: 69%
“…In addition, they also reported that 3.8% of the owners were carriers, which was slightly lower than the 4.5% prevalence rate reported from the Dutch general population [4,14]. The carriage rate in Dutch citizens is comparable to 4.7% reported from Sweden in 2013 [15], so it is interesting to note the large difference between carriage rates in Dutch and Swedish dogs. One potential explanation for the difference might be that use of extended spectrum cephalosporins (ESCs) is very limited in Sweden, while in the Netherlands, ESCs, i.e.…”
Section: Resultsmentioning
confidence: 81%
“…In some cases, they may be found in the blood system (where they cause blood sepsis), urinary, and genital tracts causing varying degrees of urinogenital disorders (19,20). As members of the Enterobacteriaceae, they are considered major public health challenges (2,21). The antibiotic resistance pattern of Citrobacter and Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%